The Impact of Chronic Tobacco Smoking on Retinal and Choroidal Thickness in Greek Population. (14th January 2016) - Moschos, Marilita M.; Nitoda, Eirini; Laios, Konstantinos; Ladas, Dimitrios S.; Chatziralli, Irini P.
Abstract : Aim . To investigate the effect of more than 25-year cigarette smoking on choroidal and retinal thickness, using spectral domain optical coherence tomography (SD-OCT). Methods . Thirty-one smokers and 25 age- and sex-matched nonsmokers, serving as control group, were submitted to slit-lamp biomicroscopy and dilated fundoscopy, SD-OCT, measurements of intraocular pressure (IOP), central corneal thickness (CCT), and axial length (AL). Heidelberg Spectralis was used to calculate choroidal thickness (CT), ganglion cell complex (GCC), outer retina layers (ORL), and macular thicknesses (MT). Results . The smokers' group consisted of 17 males and 14 females with mean age of 57.8 ± 4.5 years, while the controls' group consisted of 14 males and 11 females with mean age of 68.0 ± 4.1 years. CT and GCC thicknesses were significantly reduced in smokers compared to control group. The differences in thicknesses of ORL were marginally significant between two groups. The measurements of MT, IOP, CCT, and AL had the same distributions between smokers and nonsmokers. Conclusions . Tobacco smoking seems to result in thinner choroid and retina compared to nonsmokers. This is the first study in literature that investigates the anatomical effect of smoking for more than 25 years on the choroid and retina.